Cervical Myelopathy due to Tubercular Retropharyngeal Abscess - Amin, Md Robed; Saha, Shantonu Kumer; Sardar, Hafiz; Kabir, Ahmedul; Hawlader, Anisur Rahman; Zaman, Md Ferdous; Chowdhury, Faizul Islam; Khandaker, Md Abul Kashem (Journal of Medicine, 2010)
Tuberculosis is the commonest infectious disease in developing country. A retropharyngeal abscess is an immediate life-threatening emergency, with potential for airway compromise and other catastrophic complications. We report the clinical, radiological and histological findings of symptomatic 16 years old girl with the features of cervical cord compression due to retropharyngeal abscess of tubercular origin. The patient improved after surgical management of abscess was done followed by anti-tuberculous drugs. Keywords: Retropharyngeal abscess; extrapulmonary tuberculosis; compressive myelopathy DOI: 10.3329/jom.v11i2.5468 J MEDICINE 2010; 11 : 180-182